Cartographic modeling of the population density in the function of research of spatial-demographical relations - Jovanović Jasmina; Živković Dragica (Zbornik Radova: Geografski institut "Jovan Cvijić", 2005)
Cartographic modeling of the population density by a diagram map method (comparative way of semioscale mapping) and by a method of cartogram, enables presentation of the information about current spatial-demographical relations in a systematic, comparative, metrical, synoptic and suitable way, relevant for different aspects of specific research. Through methods of the cartographic information forms various types of population density are included: general, general agrarian, specific agrarian, agrarian-productive density and valorized agrarian population density. Chosen and applied cartographical methods, by modeling of the population density, enable to view them and express in a more apparent spatial graphical-analytical way. Applied semiometrics tends to realize the results of the numerical values of the parameters of the subject area via figures of symbols. Different types of population density are shown on the coordinate graph which enables their comparison as well as their status regarding the average values of the subject area. Cartographic modeling of the population density enables analytic and synthetic approach in researching and evaluating of the quantities and quality characteristics of the presented categories, which are functionally connected and determined, for the purpose of highlighting the typical, specific and essential. Application of the cartographic methods in modeling of the population density is shown in the example of municipalities in districts of Bor and Zajecar for 2002, where the spatial differentiation of the population density was explicit.